Responsible ownership and population management of dogs and cats in Londrina and region and its contribution to improving public health and animal welfare - Freres Mascarenhas, Nilva Maria; Scortecci Hilst, Carmen Lucia; Batista de Souza, Mirian Siliane; Mello Martins, Maria Isabel; de Biasi, Fernado; Machado, Marco Antônio; Navarro, Italmar Teodorico; de Freitas, Júlio César; Zanata Reia, Angelita; Guedes Buosi, Rafaela; Sales Costa, Anderson Cristiano; Toda, Priscila (Guará Journal, 2025)
The population rate of dogs and cats is high because these species are multiparous, and the uncontrolled breeding can cause damage to public health, because stray animals addition to spread diseases to each other, can contaminate humans (zoonoses). Thus, population management of dogs and cats at UEL through surgical sterilization, diagnosis of toxoplasmosis and leptospirosis, guidance and encouragement to the culture of animal welfare to the owners, has contributed to the reduction of the population of stray dogs and cats in Londrina and region. Simultaneously allow academics have surgical technician training, whose learning in live animal, is prohibited by law.